Ternary blend organic solar cells with improved morphological stability. Issue 16 (1st April 2019) - Nam, Minwoo; Yoo, Jaehong; Park, Yunjae; Noh, Hye Yeon; Park, Yongkook; Cho, Junhee; Kim, Jung-A.; Kim, Jehan; Lee, Hyun Hwi; Chang, Rakwoo; Ko, Doo-Hyun
Abstract : We demonstrate the improved morphological stability and lifetime of ternary organic solar cells incorporating nonfullerene small molecules in polymer:fullerene blends. Abstract : Long-term stability of organic blends is a key factor for the practical use of organic solar cells (OSCs) in commercial fields. Here, we report the strategic incorporation of non-fullerene small molecules in polymer:fullerene blends to obtain ternary OSCs with improved efficiency and extended lifetimes. Non-fullerene small molecules employed in the polymer:fullerene blend successfully increased the photon-to-current conversion process as an efficient charge cascade acceptor. A combination of theoretical simulations and experimental measurements revealed that aggregation of meta-stable fullerene molecules was significantly alleviated in the ternary blend, thereby preventing an unintentional increase in the threshold for charge transfer during operation. Thus, the ternary OSCs could exhibit highly extended lifetimes with improved morphological stability and better resistance to performance decay under harsh real operational conditions compared to their binary counterparts. Combined with its high efficiency and improved device lifetimes, the high tolerance to the ternary blend thickness offers promise for commercially acceptable ternary OSCs fabricated by a printing process.